2022
DOI: 10.24136/eq.2022.031
|View full text |Cite
|
Sign up to set email alerts
|

Links between crime and economic development: EU classification

Abstract: Research background: Although some authors propose that economic growth should reduce crime rates as wider opportunities to earn money in a legal way diminish the incentives to commit illegal activities and lead to rising costs of the latter, the results of many studies indicate that an increase in crime rates is also possible under the conditions of economic growth. There are also differing views on the relationship between various economic indicators and crime rates as well as the nature of the relationship … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
1
0
Order By: Relevance
“…Systematic empirical studies show that corruption exacerbates the problem of climate change and has a destructive impact on environmental protection. The imperfect functioning of democratic institutions , low level of economic freedom (Linhartová & Halásková, 2022;Vyas-Doorgapersad et al, 2022;Remeikienė et al, 2022), unbalanced government fiscal policies (Tiganasu et al, 2022), acceptance of bribery within society (Korjonen-Kuusipuro & Wojciechowski, 2022), a lack of business integrity (Bednárová et al, 2021;Nastisin et al, 2021;Erwin et al, 2022) and inefficient work of judicial and regulatory authorities (Piplica, 2021;Salman et al, 2022;Ogunshola et al, 2022) in the country lead to the penetration of corruption schemes into economic life.…”
Section: The Impact Of Corruption In Climate Finance On Achieving Net...mentioning
confidence: 99%
“…Systematic empirical studies show that corruption exacerbates the problem of climate change and has a destructive impact on environmental protection. The imperfect functioning of democratic institutions , low level of economic freedom (Linhartová & Halásková, 2022;Vyas-Doorgapersad et al, 2022;Remeikienė et al, 2022), unbalanced government fiscal policies (Tiganasu et al, 2022), acceptance of bribery within society (Korjonen-Kuusipuro & Wojciechowski, 2022), a lack of business integrity (Bednárová et al, 2021;Nastisin et al, 2021;Erwin et al, 2022) and inefficient work of judicial and regulatory authorities (Piplica, 2021;Salman et al, 2022;Ogunshola et al, 2022) in the country lead to the penetration of corruption schemes into economic life.…”
Section: The Impact Of Corruption In Climate Finance On Achieving Net...mentioning
confidence: 99%
“…between key figures in government and strategically located individuals: trade union leaders, businessmen, community leaders, and so forth" (Theobald, 1982, p. 552). Kelsall (2011) and Masenya (2017) found that namely patrimonialism is a significant source of income supplement through corruption for the politicians in such developing economies (Remeikiene et al 2022) as African states. Particularism is defined as attachment to a particular group, political party, etc.…”
Section: Literature Review: Corruption Sourcesmentioning
confidence: 99%
“…A sufficiently large range of current research is related to the economic dimension -"The impact of corruption on investment and financing in the European Union: new insights" (Farinha and Lópezde-Foronda 2023), "Links between crime and economic development: EU classification" (Remeikiene et al 2022), "Corruption, national culture and corporate investment: European evidence" (García-…”
Section: Literature Reviewmentioning
confidence: 99%